Directionality of DnaA protein/DNA interaction. Active orientation of the DnaA protein/dnaA box complex in transcription termination. - Schaefer, C (1989)
The complex of DnaA protein with its 9 bp consensus binding site, the dnaA box 5'-TT(A/T)T(A/C)CA(A/C)A, blocks transcribing RNA polymerase. In a model system, the rate of transcription was monitored distal to the dnaA box 5'-TTTTCCACA by the expression of a reporter gene. DnaA-dependent transcription termination occurred irrespective of whether the dnaA box region was or was not translated. Only the dnaA box orientation 5'-TTTTCCACA on the non-coding strand, but not the reverse orientation, was active in termination. This suggests that DnaA protein contacts only one strand of the DNA duplex. Oligonucleotide-directed mutation of a dnaA box present within the dnaA coding region resulted in increased expression of dnaA. This demonstrates that DnaA protein-directed transcription termination is an element of the autoregulation of the dnaA gene.